Analisis Tantangan Negara Hukum Dalam Menegakkan Hukum Tata Negara Di Era Digital - Savina Anggun Lestari; Muhammad Rijal Sadida; Risyan Putri Maharani; Intan Wahyuningtyas Andini (Universitas Katolik Widya Karya Malang, 2023)
A rule of law is a country that upholds the rule of law as the main foundation in the administration of the state and government. In essence, a rule of law state also adheres to the meaning that every decision and action of the government must be based on law and mere will. It has been written clearly that the legal basis for the rule of law in Indonesia is contained in Article 1 Paragraph (3) of the 1945 Constitution which states that,